Sustaining the University of Johannesburg and Western Sydney University partnership in the time of COVID: A qualitative case study (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article offers a qualitative case study of how COVID has changed an existing international education partnership between the University of Johannesburg (UJ) in South Africa and Western Sydney University (WSU) in Australia which involves collaboration with the not-for-profit Nsasani Trust and focuses on sustainability. Before COVID, both universities ran joint student mobility programs in the Kruger National Park (KNP) and were developing further plans for staff mobility and co-developed postgrad programs involving residency in both countries. These plans changed as a result of the COVID pandemic, which started in early 2020. Societal responses to the COVID pandemic, including national border closures, have forced academics, administrators and students to reconsider how internationalisation programs function during and after the pandemic. Using a qualitative case study based on personal experience, we argue that pre-existing university-to-university connections built before COVID will sustain linkages, but that the previous structure of engagement – based on physical mobility – can shift to new arrangements that can be run fully digitally or used to support limited mobility when international travel resumes in the future. We position the UJ-WSU relationship in the historical context of internationalisation to both highlight the enduring nature of international engagements and suggest that changes are required to make international education sustainable.
Keywords: Environmental History; Internationalisation; Study Abroad; Sustainable Development Goals